TACTICS OF TWO-STAGE SURGICAL TREATMENT OF OPEN FRACTURES OF LIMB BONES IN COMBINED TRAUMA - Shukurov E.M; Soipov R.R; Joynarov Y.U (Scholar Express Journals, 2024)
The article describes the development of a two-stage treatment algorithm for open fractures of the foot bones in 120 patients with joint injuries (DGU No. 28443, from 10/19/2023). It was developed to prevent severe complications in patients with joint injuries, taking into account the severity of the patient's overall condition, by using a minimally invasive method to stabilize the bone fragments with an external device (FAP: 2023 0097, from 03/17/23). After stabilizing the patient's overall condition, the second stage involves the application of modern treatment methods, which is substantiated to improve treatment outcomes
Keywords: joint injury; open fractures; external fixation device